Presença E Governo De Deus No Guia Dos Perplexos De Maimônides - Aguena, Anita Sayuri [UNIFESP] (2017)
The Jewish God, although being conceived as above all things and even not being able to be called by a name, is also seen as a personal being, which speaks and attend to the clamors of the virtuous and less favored and interferes directly in history. He is understood as a being whose presence (shekinah) manifests within the world, according the said: “Surely his salvation is nigh them that fear him; that glory may dwell in our land” (SI 85:9). Maimonides, in his fundamental philosophic work the Guide for the Perplexed, presents a one God, transcendent and ineffable on which nothing can speak directly and from which nothing can be predicted affirmatively. On the other hand, the thinker presents a universe that comes to be through levels of emanations, which further distances this God from having a direct action or influence on the sensitive and sublunar world. This leads to a quest of how such a distant God can be compatible with the Jewish image of an immanent being, present in history and active in individual destinies. This work aims to study Maimonides' conception of God and of the Universe to understand how this transcendent God can act in the world, maintaining the prerogatives of presence and governance bestowed on Him by Judaism.